2021
DOI: 10.1007/s10549-021-06365-7
|View full text |Cite
|
Sign up to set email alerts
|

HER2-low status and response to neoadjuvant chemotherapy in HER2 negative early breast cancer

Abstract: Recently, phase I studies with novel antibody drug conjugates targeting HER2 suggested benefit in HER2-low patients -defined as immunohistochemistry(IHC) +1 or +2 FISH/ISH non-amplified, with advanced breast cancer(BC). Data on the prognostic value of HER2-low in early stage disease is scarce. The purpose of this study was to evaluate the impact of HER2-low status on response to neoadjuvant chemotherapy(NACT) and survival outcomes in early stage HER2negative BC. MethodsRecords from all BC patients treated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 30 publications
9
60
4
Order By: Relevance
“…A number of studies emerged in the past years have identified differences between HER2-low and HER2-0 disease, currently classified as HER2− disease, suggesting that HER2-low tumors constitute a distinct nosological entity [ 6 - 8 ]. In this study, the HER2-low subgroup was prevalent representing 56.9% of all patients, which is in agreement with previous reports, whose frequency ranged from 45% to 55% [ 6 , 8 , 14 , 16 ]. There was a slightly higher proportion of HER2 2+/ISH non-amplified in our study, which is opposite to the previous series where the vast majority of HER2-low patients had an IHC 1+.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A number of studies emerged in the past years have identified differences between HER2-low and HER2-0 disease, currently classified as HER2− disease, suggesting that HER2-low tumors constitute a distinct nosological entity [ 6 - 8 ]. In this study, the HER2-low subgroup was prevalent representing 56.9% of all patients, which is in agreement with previous reports, whose frequency ranged from 45% to 55% [ 6 , 8 , 14 , 16 ]. There was a slightly higher proportion of HER2 2+/ISH non-amplified in our study, which is opposite to the previous series where the vast majority of HER2-low patients had an IHC 1+.…”
Section: Discussionsupporting
confidence: 93%
“…The results were consistent with previous data, concerning HR expression, HER2-low tumors expressing a higher level of HR (65-83%) [ 6 - 8 , 14 ]. Specifically, a study about molecular analysis including PAM50 gene expression features of HER2-low BC found that ERBB2 levels are predominant in HR+/HER2-low tumors compared with TNBC/HER2-low tumors [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, studies currently present conflicting results. While a recent pooled analysis of 2310 patients from 4 neoadjuvant clinical trials showed better disease-free survival (DFS) and overall survival (OS) in HER2-low BC [ 11 ], other studies in the non-metastatic setting [ 12 – 14 ] and metastatic setting [ 15 17 ] did not observe any significant differences. In contrast, two older studies reported inferior DFS in non-metastatic BCs that were HER2 IHC 2+ ISH− compared with those which were HER2 IHC 1+ or 0 [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%